Slides from Launch of 2021 Social Accounting Matrix for Kenya - Breisinger, Clemens; Omune, Lensa (CGIAR System Organization, 2023)
Prepared by Clemens Breisinger; presented by Lensa Omune, Research Officer, both with IFPRI. Prepared and presented for the KIPPRA Annual Regional Conference at Kilifi, Kenya on June 23, 2023.